2022
DOI: 10.3390/ijms24010621
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ATF4-Regulated Atrogenes Is Uncoupled from Muscle Atrophy during Disuse in Halofuginone-Treated Mice and in Hibernating Brown Bears

Abstract: Activating transcription factor 4 (ATF4) is involved in muscle atrophy through the overexpression of some atrogenes. However, it also controls the transcription of genes involved in muscle homeostasis maintenance. Here, we explored the effect of ATF4 activation by the pharmacological molecule halofuginone during hindlimb suspension (HS)-induced muscle atrophy. Firstly, we reported that periodic activation of ATF4-regulated atrogenes (Gadd45a, Cdkn1a, and Eif4ebp1) by halofuginone was not associated with muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Cussonneau et al [5] addressed the role of transcription factor 4 (ATF4) in mice skeletal muscles undergoing hindlimb suspension (HS) atrophy and in muscles from hibernating brown bears, a naturally atrophy-resistant model. The activity of ATF4 was increased using a pharmacological drug (halofuginone) in mice and the authors found that ATF4-regulated atrogenes (atrophy-related genes) were upregulated in both HS mice and hibernating bears (note that ATF4 is upregulated is hibernating brown bears).…”
mentioning
confidence: 99%
“…Cussonneau et al [5] addressed the role of transcription factor 4 (ATF4) in mice skeletal muscles undergoing hindlimb suspension (HS) atrophy and in muscles from hibernating brown bears, a naturally atrophy-resistant model. The activity of ATF4 was increased using a pharmacological drug (halofuginone) in mice and the authors found that ATF4-regulated atrogenes (atrophy-related genes) were upregulated in both HS mice and hibernating bears (note that ATF4 is upregulated is hibernating brown bears).…”
mentioning
confidence: 99%